Penerapan Restorative Justice Dalam Sistem Peradilan Pidana Anak (Anak Sebagai Pelaku Kejahatan) - Pare, Prisko Yanuarius Djawaria; Ule, Kristina; Ndang, Ignasia Agtin; Ganur, Anjelina; Jangging, Crispianus Decostan (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2022)
The text emphasizes the importance of prioritizing children's rights and restorative justice principles in resolving cases of children in conflict with the law. It highlights that arrest, exile, or imprisonment should be a last resort and for a short duration. While restorative justice is specified in Indonesian law, its implementation varies due to the need for adjustments, facilities, and trained personnel. The research aims to enhance understanding of resolving juvenile criminal cases through restorative justice, focusing on the principles of kinship and the best interests of the child. The study uses a literature review approach to discuss cases resolved outside formal legal channels, emphasizing qualitative descriptive analysis. The text underscores the need for legal tools, infrastructure, and a restorative justice approach to address issues, train children as future human resources, and prevent negative labels. It advocates for diverting child criminals from the criminal system and prioritizing the best interests of the child, emphasizing a positive attitude and belief in a better world.